Flexible work arrangement expectations: The impact on psychological contract breach and work outcomes - Arias, D.; Costa, S. (British Academy of Management, 2023)
The main goal of this paper is to understand the impact of flexible work arrangements expectations in the reality of post Covid-19 have on organizational commitment, job satisfaction, and work-life balance. Moreover, we examine the mediating role of psychological contract breach. In a sample of one hundred and thirty employees, findings show that there is a discrepancy between what employees expect and receive in terms of flexibility, which has a positive relationship with psychological contract breach. Moreover, results also show a negative relationship with organizational commitment, job satisfaction, and work-life balance. Our findings are relevant to managers and organizations as they stress the need to recognize that offer different form of flexibility contributes to a more positive relationship with the organization and job. Additionally, it allows employees to have balance between their personal and professional lives.